Analisis Biaya Lingkungan pada Rumah Sakit Islam Gorontalo - Valentina Monoarfa; Azhari Isima; Alya Prisiliya Genda (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
Gorontalo Islamic Hospital is a type D general hospital located at Jalan KH. Agus Salim (HB Jassin) No. 457, Liluwo, Kota Tengah, Gorontalo. Established on November 7, 2013, the hospital operates under the auspices of a social organization in Gorontalo. This study aims to determine the environmental costs at Gorontalo Islamic Hospital and to determine whether waste management is in accordance with procedures and safe for the environment. This type of research is qualitative research with descriptive method. Based on the research conducted, it is concluded that the Gorontalo Islamic Hospital can manage the waste generated from the hospital properly and correctly, help reduce the negative impact of the waste, and help reduce the impact on the surrounding environment, this research also helps to calculate the expenditure of the environmental cost budget at the Gorontalo Islamic Hospital, and helps that researchers can make this research a reference.